PRAKTIK HIGIENE SANITASI PANGAN PENJAMAH MAKANAN DALAM PENJUALAN MAKANAN PADA AWAL PANDEMI COVID-19 DI JABODETABEK - Prisca Petty Arfines; Zahra Zahra; Dwi Nastiti Iswarawanti; Ika Saptarini (Puslitbang Upaya Kesehatan Masyarakat, 2021)
ABSTRACT The COVID-19 pandemic has affected people's behavior including shopping behavior. The most important things highlighted in food buying behavior include food safety and the implementation of health measures to minimize the COVID-19 transmission. This study aims to identify the description of food hygiene and sanitation practices (HSP) for food handlers during the COVID-19 pandemic. This study is an observational study with a cross-sectional design conducted in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, and Bekasi) in the first week of May 2020. Data collection was carried out online. The sample in this study was 189 food handlers. The variables analyzed included the HSP practices of food handlers, socio-demography, knowledge proxies, perceptions, and sources of information related to COVID-19. The results of the analysis showed that insufficient practice of HSP reached 49.7%. Factors related to the HSP practice are the provision of handwashing using soap facilities for food buyers/delivery (OR=2.4 95% CI 1.01-5.7) and the provision of medical tests for the worker (OR=2.61 95% CI 1.27-5.37). This study depicts the HSP’s practice of food handlers at the beginning of the pandemic in Jabodetabek is still lacking. Therefore, it is necessary to increase the promotion and priority of supervision on the HSP practice of food handlers in an integrated manner from across sectors. Strengthened coaching may lead to better HSP practices for food handlers. Keywords: Food sanitation, food hygiene, food safety, food purchasing, food handler ABSTRAK Pandemi COVID-19 telah mempengaruhi perilaku masyarakat termasuk perilaku berbelanja. Hal terpenting yang menjadi sorotan dalam perilaku penjualan makanan antara lain aspek keamanan pangan dan pelaksanaan protokol kesehatan untuk menekan penyebaran COVID-19. Studi ini bertujuan untuk mengidentifikasi gambaran praktik higiene sanitasi (HSP) pangan penjamah makanan dalam penjualan makanan di masa pandemi COVID-19. Studi ini merupakan studi observasional dengan desain potong lintang yang dilakukan di area Jabodetabek (Jakarta, Bogor, Depok, Tangerang dan Bekasi) pada minggu pertama bulan Mei 2020. Pengumpulan data dilakukan secara daring. Sampel dalam penelitian ini adalah sebanyak 189 penjual makanan. Variabel yang dianalisis antara lain meliputi praktik HSP penjual makanan, sosio-demografi, proksi pengetahuan, persepsi, dan sumber informasi terkait COVID-19. Hasil analisis menunjukkan bahwa praktik HSP dengan kategori kurang mencapai 49,7%. Faktor yang berhubungan dengan praktik HSP dari penjual makanan adalah penyediaan sarana CTPS bagi pembeli/pengantar makanan (OR=2,4 95% CI 1,01-5,7) dan penyediaan tes kesehatan selama bekerja (OR=2,61 95% CI 1,27-5,37). Studi ini menunjukkan bahwa gambaran praktik higiene sanitasi pangan penjual pada awal masa pandemi di Jabodetabek masih kurang. Oleh karena itu perlu dilakukan penguatan promosi dan prioritas pengawasan pada praktik HSP penjual makanan secara terpadu dari lintas sektor. Penguatan pembinaan dapat meningkatkan praktik HSP penjual yang lebih baik. Kata kunci: Sanitasi pangan, higiene pangan, keamanan pangan, pembelian makanan, penjamah makanan